TORACOLOMBAR BURST FRACTURES AND SPINOPELVIC BALANCE - COSTA,DANIEL (2020)
ABSTRACT Objective To describe the spinopelvic parameters in patients with conservatively treated thoracolumbar burst fractures. Methods Twenty-six patients with thoracolumbar burst fractures treated conservatively between 2008 and 2017 participated in the study. Inclusion criteria were acute burst-type fractures, located between T11 and L2, which compromised a single vertebral segment, did not present a neurological deficit, and had a minimum of 6 months of follow-up, excluding injuries that presented distraction or rotation, pathological fractures, and surgically treated cases. The sagittal and spinopelvic alignment parameters, including vertical sagittal axis, sacral slope, pelvic tilt, pelvic incidence, lumbar lordosis, and regional kyphosis, were analyzed. Results The values obtained for the sample showed that there was an increase in regional kyphosis and that the mean sagittal parameters and lumbar lordosis were within the values considered normal in the literature. Conclusion Patients with thoracolumbar burst fractures treated conservatively had no alterations in the spinopelvic parameters. Level of Evidence II; Retrospective study.